Raspberry Pi mechatronics projects HOTSHOT : enter the world of mechatronic systems with the raspberry Pi to design and build 12 amazing projects /: enter the world of mechatronic systems with the raspberry Pi to design and build 12 amazing projects. (2015) - Yamanoor, Sai; Yamanoor, Srihari
No abstract available